The Influence of Learning Models Inquiry Training Regarding the Learning Outcomes of Class Ix Students at SMP Negeri 5 Sumenep - Fauzan, Ahmad; Prihandono, Trapsilo; Bektiarso, Singgih (Peneliti.net, 2024)
This study aims to determine the effect of the Inquiry Training learning model on the Learning Outcomes of Class IX Students of SMP Negeri 5 Sumenep. The research method used is a quasi experiment. The research design used is nonequivalent control group design. The sample in this study were students of class IX A as an experimental class totaling 31 students and class IX C as an experimental class totaling 30 students. The research instrument used was a description test question to see student learning outcomes. The results of the Independent Sample T-Test hypothesis test showed a significance value of 0.008 <0.05 which states that H0 is rejected and H1 is accepted so it can be concluded that the use of the Inquiry Training learning model has a significant effect on student learning outcomes on Electrical Circuit material